Rapid degradation of Congo red wastewater by Rhodopseudomonas palustris intimately coupled carbon nanotube - Silver modified titanium dioxide photocatalytic composite with sodium alginate. (July 2022) - Liu, Kai; Yang, Yuewei; Sun, Fengfei; Liu, Yanyan; Tang, Meizhen; Chen, Junfeng
Abstract: With a large number of Congo red used in textiles, Congo red wastewater was not easily degraded, resulting in environmental and health-related problems. In order to improve the degradation efficiency of Congo red wastewater, A novel intimately coupled photocatalysis and biodegradation (ICPB) system was prepared by coupling Rhodopseudomonas palustris ( R. Palustris ), carbon nanotube - silver modified titanium dioxide photocatalytic composite (CNT-Ag -TiO2, CAT) and sodium alginate (SA) ( R. palustris/ CAT@SA). Compared with immobilized CAT and R. palustris, the R. palustris /CAT@SA improved the degradation and removal rates of Congo red by 14.3% and 42.1%, and the COD removal rates by 76% and 44.6%, respectively. The mechanism of the degradation of Congo red by the new ICPB was that the Congo red on the surface of the support was degraded into long-chain alkanes by the superoxide and hydroxyl radicals of CAT product, and then the long-chain alkanes were completely mineralization by R. Palustris, which reduced the accumulation of intermediates in the photocatalysis. Most of the Congo red was adsorbed to the interior of the carrier was degraded into aromatic hydrocarbons by R. Palustris, and then oxidized and degraded by CAT, and a small part of the Congo red would be directly mineralized by R. Palustris . A novel technical solution of R. palustris /CAT@SA provided a potential application to the degradation of dye wastewater. Graphical abstract: Image 1 Highlights: The novel R. palustris /CAT@SA system was used to degrade Congo red wastewater. Photocatalytic toxicity was prevented and the system had good biocompatibility. R. palustris /CAT@SA accelerated degradation of Congo red wastewater. Degradation pathways of Congo red wastewater were proposed.